Educational significance of national musical performance - Botirov Maqsadjon Ibragimovich (Researchparks Publishing, 2022)
This article is about the impact of music on the human psyche, the role of the instrumentalist in changing the inner world, the role of music in the education of the younger generation, the importance of starting it from the family.